2018
DOI: 10.3390/app8081305
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Increase in Specific Heat of Binary Molten Salt-Based Graphite Nanofluids for Thermal Energy Storage

Abstract: An anomalous increase of the specific heat was experimentally observed in molten salt nanofluids using a differential scanning calorimeter. Binary carbonate molten salt mixtures were used as a base fluid, and the base salts were doped with graphite nanoparticles. Specific heat measurements of the nanofluids were performed to examine the effects of the composition of two salts consisting of the base fluid. In addition, the effect of the nanoparticle concentration was investigated as the concentration of the gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Additionally, the specific heat enhancements were affected by the composition of the salt components comprising the base solvent of the nanofluids for both the carbonate and nitrate salts. The effects of the base solvent on the specific heat of binary‐salt‐based nanofluids have already been observed in our previous studies 14,15,17 . Based on the experimental results in this study and previous studies, it may be hypothesized that the thermophysical property changes in the solvent material, which are dependent on the composition, affect the specific heat of the nanofluids.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, the specific heat enhancements were affected by the composition of the salt components comprising the base solvent of the nanofluids for both the carbonate and nitrate salts. The effects of the base solvent on the specific heat of binary‐salt‐based nanofluids have already been observed in our previous studies 14,15,17 . Based on the experimental results in this study and previous studies, it may be hypothesized that the thermophysical property changes in the solvent material, which are dependent on the composition, affect the specific heat of the nanofluids.…”
Section: Resultssupporting
confidence: 80%
“…However, the redundant nanoparticles (2 wt%) unfavorably affected the specific heat of the salt mixture, decreasing it by 5.7%. 7 In addition, various molten salt mixtures, that is, a binary nitrate salt (NaNO 3 -KNO 3 ), [8][9][10][11][12][13] binary carbonate salt (Li 2 CO 3 -K 2 CO 3 ), [14][15][16][17] ternary nitrate salt (LiNO 3 -NaNO 3 -KNO 3 ), 18,19 ternary carbonate salt (Li 2 CO 3 -Na 2 CO 3 -K 2 CO 3 ), 20,21 quaternary nitrate salt (NaNO 3 -KNO 3 -LiNO 3 -Ca[NO 3 ] 2 ), 22 and binary chloride salt (NaCl-CaCl 2 ), 23 were employed to examine the effects of material, size, concentration, and dispersion homogeneity of nanoparticles on the specific heat behaviors. In most of these studies, the specific heat values of the molten salt nanofluids were increased irrespective of the nanoparticles used.…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental results contradict this prediction where specific heat capacity values are enhanced on mixing with solid nanoparticles (e.g., in the form of stable colloidal suspension). Modified models were, therefore, developed to mitigate these discrepancies by accounting for the high surface energy of nanoparticles compared to the bulk property values of the solid phase [ 48 , 49 ] and recognizing the existence of a “compressed phase” or “compressed layer” that is induced on the surface of the nanoparticle by molecules of the solvent phase that are adsorbed on the surface [ 50 , 51 ]. In the compressed layer, the dominance of the adhesive forces over the cohesive forces causes the molecules of the solvent phase in the vicinity of the nanoparticle surface to be packed into smaller volumes which results in a higher mass density and a greater total potential energy.…”
Section: Discussionmentioning
confidence: 99%
“…H. J. Kim and B. Jo [13] focused on the use of the nanofluid comprising the base fluid of a binary carbonate molten sate mixture and graphite nanoparticles for thermal energy storage application. It was observed that the specific heat of the nanofluid was significantly enhanced by the presence of the graphite nanoparticles.…”
Section: Current Advances In the Applications Of Nanofluidsmentioning
confidence: 99%